Correlation of Individual Factors and Subjective Workload with Work Stress on Spinning Workers - Septi Dewi Yuliani; Noeroel Widajati (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Excessive workload is a major factor causing work stress. The condition that arises as a result of the inability of workers to deal with the demands of their work causes work stress. This study aims to analyze the relationship between individual factors and subjective workload with work stress on the spinning workers of PT. Delta Merlin Sandang Tekstil I Sragen. Methods: This study was an observational analytic study with a cross sectional study design. Research was conducted in January 2020 in PT. Delta Merlin Sandang Tekstil I Sragen. The samples of this research consisted of 133 respondents, which were determined by using a simple random sampling method. Work stress was a dependent variable in this study and individual factors (age, gender, education level, years of service, and marital status) were the independent variables; moreover, the work factor used was subjective workload. Data on individual characteristics, subjective workload, and work stress were obtained through distributing questionnaires to workers. Data analysis was performed using the Spearman correlation. Results: The results of the study state that there is no relationship between age (p = 0.790), sex (p = 0.659), level of education (p = 0.499), years of service (p = 0.730), marital status (p = 0.251) and work stress, and there is a relationship between subjective workload and work stress (p = 0,000). Conclusion: There is a significant relationship between subjective workload and work stress, but there is no relationship between individual factors and work stress among the spinning workers of PT. Delta Merlin Sandang Tekstil I Sragen.Keywords: individual factors, subjective workload, work stress